2019
DOI: 10.1609/aaai.v33i01.33012304
|View full text |Cite
|
Sign up to set email alerts
|

Bézier Simplex Fitting: Describing Pareto Fronts of´ Simplicial Problems with Small Samples in Multi-Objective Optimization

Abstract: Multi-objective optimization problems require simultaneously optimizing two or more objective functions. Many studies have reported that the solution set of an M -objective optimization problem often forms an (M − 1)-dimensional topological simplex (a curved line for M = 2, a curved triangle for M = 3, a curved tetrahedron for M = 4, etc.). Since the dimensionality of the solution set increases as the number of objectives grows, an exponentially large sample size is needed to cover the solution set. To reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…The Pareto front of nondegenerate problems with m objectives is an m−1-dimensional manifold. Instead of a one-dimensional Bézier curve, the Pareto set can then be modeled by an (m−1)-dimensional Bézier simplex [15]. For the navigation of higher-dimensional manifolds, a one-dimensional path through all obtained solutions could still be used.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pareto front of nondegenerate problems with m objectives is an m−1-dimensional manifold. Instead of a one-dimensional Bézier curve, the Pareto set can then be modeled by an (m−1)-dimensional Bézier simplex [15]. For the navigation of higher-dimensional manifolds, a one-dimensional path through all obtained solutions could still be used.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Optimizing only the control points of the Bézier curve, that define its curvature, enforces the decision variables of solutions in the approximation set to vary in a smooth, continuous fashion, thereby likely improving intuitive navigability of the approximation set. Previous work on parameterizations of the approximation set has been applied mainly in a post-processing step after optimization, or was performed in the objective space [3,15,19], but this does not aid in the navigability of the approximation set in decision space. Moreover, fitting a smooth curve through an already optimized set of solutions might result in a bad fit, resulting in a lower-quality approximation set.…”
Section: Introductionmentioning
confidence: 99%
“…is a multinomial coefficient, and (Kobayashi et al 2019) proposed two Bézier simplex fitting algorithms: the all-at-once fitting and the inductive skeleton fitting. They are different in not an only fitting algorithm but also sampling strategy.…”
Section: Bézier Simplex and Its Fitting Methodsmentioning
confidence: 99%
“…There are a lot of practical problems being simplicial: location problems (Kuhn 1967) and a phenotypic divergence model in evolutionary biology (Shoval et al 2012) are shown to be simplicial, and an airplane design (Mastroddi and Gemma 2013) and a hydrologic modeling (Vrugt et al 2003) have numerical solutions which imply those problems are simplicial. The Pareto set and front of any simplicial problem can be approximated with arbitrary accuracy by a Bézier simplex of an appropriate degree (Kobayashi et al 2019). There are two fitting algorithms for Bézier simplices: the all-at-once fitting is a naïve extension of Borges-Pastva algorithm for Bézier curves (Borges and Pastva 2002), and the inductive skeleton fitting (Kobayashi et al 2019) exploits the skeleton structure of simplicial problems discussed above.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation